1994
DOI: 10.1128/mcb.14.11.7340
|View full text |Cite
|
Sign up to set email alerts
|

A homeodomain protein related to caudal regulates intestine-specific gene transcription.

Abstract: The continually renewing epithelium of the intestinal tract arises from the visceral endoderm by a series of complex developmental transitions. The mechanisms that establish and maintain the processes of cellular renewal, cell lineage allocation, and tissue restriction and spatial assignment of gene expression in this epithelium are unknown. An understanding of the regulation of intestine-specific gene regulation may provide information on the molecular mechanisms that direct these processes. In this regard, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
357
1
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(374 citation statements)
references
References 24 publications
14
357
1
2
Order By: Relevance
“…In our datasets, we observe strong correlation between loss of CDX2 and the CMS1 and CMS4 subtypes, in accordance with the strong association of CDX2 loss with MSI (CMS1) and worse prognosis (CMS4), and loss of differentiation, a hallmark of CDX2 loss in cancer (Suh et al ., 1994). In contrast to a recent study (Pilati et al ., 2017), we showed that loss of CDX2 is associated with shorter survival in both CMS1 and CMS4.…”
Section: Discussionmentioning
confidence: 99%
“…In our datasets, we observe strong correlation between loss of CDX2 and the CMS1 and CMS4 subtypes, in accordance with the strong association of CDX2 loss with MSI (CMS1) and worse prognosis (CMS4), and loss of differentiation, a hallmark of CDX2 loss in cancer (Suh et al ., 1994). In contrast to a recent study (Pilati et al ., 2017), we showed that loss of CDX2 is associated with shorter survival in both CMS1 and CMS4.…”
Section: Discussionmentioning
confidence: 99%
“…Human Cdx2 is a member of the caudalrelated homeobox gene family that activates an intestinal-specific gene transcription, which regulates normal intestinal development and differentiation and plays an important role in triggering cells towards the phenotype of differentiated enterocytes as well as in the maintenance of the phenotype. [15][16][17][18][19] Cdx2 expression in normal adult tissues is restricted to intestinal and colonic epithelium and a subset of pancreatic acinar and ductal cells. 22,24,27 In neoplasms, it is expressed by small and large intestinal epithelial tumors, by esophageal, urinary bladder and ovarian mucinous adenocarcinomas, and by a subset of pancreatobiliary adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] The expression of Cdx2 in adult non-neoplastic tissues has been shown to be restricted to normal intestinal epithelium, normal pancreatic epithelial cells, and gastric and esophageal intestinal metaplasia. [20][21][22][23][24][25][26][27] In the gastrointestinal tract, Cdx2 is strongly and diffusely expressed in the nuclei of normal small and large intestinal epithelial cells, including absorptive, goblet, endocrine and Paneth cells; in the pancreatic epithelium its expression is focal and patchy.…”
mentioning
confidence: 99%
“…The sucrase-isomaltase and LI-cadherin genes, downregulated in migrating cells of the wound edge, are direct targets of the transcription factor Cdx2 (Suh et al, 1994;Hinoi et al, 2002). Therefore, we analysed Cdx2 in the wound healing model (Figure 2).…”
Section: Cdx2 Expression Is Reduced In Migrating Cells At the Wound Edgementioning
confidence: 99%